Tales of Middle Mesolithic cultural transformations and marine adaptation: The case of a simple hatchet of whale bone - Skar, Birgitte; Rosvold, Jørgen; Nymoen, Pål (Primitive Tider, 2022)
Submerged archaeological sites from the early Holocene, along the south-western and western Norwegian coastline are important sources of new information about stone-age human populations and coastal adaptation. In this article we present a Mesolithic hatchet made of bone that was found at the harbor floor at Kirkehavn in southern Norway in 1997. While radiocarbon dating proved this hatchet to be the oldest directly dated in Scandinavia (9884–9480 cal BP), aDNA analysis has identified the species from which this hatchet was made as either bowhead whale (Balaena mysticetus) or northern right whale (Eubalaena glacialis). The deposit of the hatchet must be understood in light of other contemporary ritual deposits along the south coast of Norway like the sub-merged Middle Mesolithic ritual site at Hummervikholmen and the cultural transformations taking place during this time. The result supplements the tale of new introductions in cultural practice and in material culture concurrently indicating the introduction of more complex hunter gatherer societies, while the distinctly marine adaptation continued on this part of the coast publishedVersion